Penyakit Parkinson : Tinjauan Terpadu Biomedis dan Kemajuan Terapi Terkini - Sari Mariyati Dewi Nataprawira; Triyana Sari; Erick Sidarta (Universitas Muhammadiyah Manado, 2025)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by the degeneration of dopaminergic neurons in the substantia nigra pars compacta, which plays a crucial role in regulating movement. The hallmark pathology of PD is the formation of Lewy bodies, abnormal protein aggregates composed primarily of α-synuclein. The pathophysiological mechanisms of this disease are multifactorial, involving a complex interaction between genetic and environmental factors. Molecularly, several key mechanisms involved include mitochondrial dysfunction, oxidative stress, chronic neuroinflammation, and genetic mutations in the LRRK2, DJ-1, PINK1, and SNCA genes, which have been shown to influence susceptibility to PD. In addition to genetic factors, the risk of developing PD is also influenced by environmental exposures, including pesticides, heavy metals, and exposure to certain toxins that can accelerate neuronal damage. The clinical manifestations of PD are characterized by classic motor symptoms, namely resting tremor, bradykinesia, rigidity, and gait disturbances, which are often accompanied by non-motor symptoms such as sleep disturbances, depression, autonomic dysfunction, and cognitive decline. Diagnosis generally follows the UK Brain Bank clinical criteria, supported by neuroimaging techniques such as DaTSCAN and MRI, and the development of biomarkers based on α-synuclein detection to improve the accuracy of early diagnosis. The main treatment option currently is pharmacological therapy, particularly levodopa, often combined with dopamine agonists or MAO-B inhibitors to optimize symptom control. In advanced cases, surgery in the form of deep brain stimulation can provide significant improvement. Innovative therapies such as gene therapy, stem cell therapy, and the integration of wearable devices and artificial intelligence are being developed to improve symptom monitoring and personalize treatment. Current research focuses on the development of more sensitive diagnostic methods and neuroprotective therapies that can slow disease progression.